2016
DOI: 10.1098/rspa.2016.0376
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability of extreme wave height representing storm severity in the northeast Atlantic and North Sea since the foundation of the Royal Society

Abstract: Long-term estimation of extreme wave height remains a key challenge because of the short duration of available wave data, and also because of the possible impact of climate variability on ocean waves. Here, we analyse storm-based statistics to obtain estimates of extreme wave height at locations in the northeast Atlantic and North Sea using the NORA10 wave hindcast (1958–2011), and use a 5 year sliding window to examine temporal variability. The decadal variability is correlated to the North Atlantic oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Figure 5 shows the Spearman rank correlation coefficient between the station-based NAO index and the 95th percentile of H s for DJFM for the historical period (1980 to 2009) and the period 2070-2099 under RCP4.5 and RCP8.5 for each ensemble member. Previous studies have shown a strong correlation between NAO and H s for the present wave climate off the west coast of Ireland (Gallagher et al, 2014), and for more extreme wave heights in the Northeast Atlantic and North Sea regions (Santo et al, 2016b). This is consistent with Figure 5a-c which shows the strong positive correlation coefficient, by ensemble member, between NAO and H s averaged over the historical period.…”
Section: North Atlantic Oscillation (Nao)supporting
confidence: 80%
See 1 more Smart Citation
“…Figure 5 shows the Spearman rank correlation coefficient between the station-based NAO index and the 95th percentile of H s for DJFM for the historical period (1980 to 2009) and the period 2070-2099 under RCP4.5 and RCP8.5 for each ensemble member. Previous studies have shown a strong correlation between NAO and H s for the present wave climate off the west coast of Ireland (Gallagher et al, 2014), and for more extreme wave heights in the Northeast Atlantic and North Sea regions (Santo et al, 2016b). This is consistent with Figure 5a-c which shows the strong positive correlation coefficient, by ensemble member, between NAO and H s averaged over the historical period.…”
Section: North Atlantic Oscillation (Nao)supporting
confidence: 80%
“…Le Cozannet et al (2011) carried out a regional study using the ERA-40 dataset (Uppala et al, 2005) to drive the WAve Model (WAM) for the Bay/Gulf of Biscay (west of France) and also found a strong influence of the NAO/EA on the wave climatology in that region. The East Atlantic Western Russian (EAWR) pattern and the Scandinavian pattern are other modes of Northern Hemisphere atmospheric variability, and along with the EA have a weaker influence on the North Atlantic than the NAO (Santo et al, 2016b). For the purpose of the study presented in this paper, we focus on the NAO which is the most important North-24 E. Gleeson et al: Extreme waves in the North Atlantic Ocean ern Hemisphere mode of variability (Greatbatch, 2000;van Loon and Rogers, 1978;Hurrell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolation into the future assumes a continuous linear trend in extreme wave heights, as has been detected for the available dataset, though neglecting the decadal variation due to the NAO fluctuation and the other cyclical atmospheric modes highlighted by Santo et al . [35]. The omission of these further factors will increase the uncertainty of the 2067 design wave heights.…”
Section: Wave Loadingmentioning
confidence: 99%
“…The average H max value (measured over the typical duration of a storm, for example) could allow for assessing the severity of a sea condition, similarly to the so-called most probable maximum individual wave height [16], and hence be used as a criterion to enter survival mode.…”
Section: B Survival Modementioning
confidence: 99%